Struktur Ekonomi, Sektor Basis, dan Kemandirian Fiskal: Analisis PDRB Kabupaten Aceh Tengah 2020–2024 - Ibnuh Sukoco; Sirodjuzilam Hasyim; M. Syafi; Thomas Firdaus Hutahaean (Yayasan Literasi Sains Indonesia, 2026)
This study analyzes the economic structure, base sectors, dynamics of Gross Regional Domestic Product (GRDP), the relationship between GRDP and Regional Original Revenue (PAD), as well as social implications in Central Aceh Regency during the 2020–2024 period. The data used include GRDP by business field, GRDP per capita, and PAD sourced from the Central Statistics Agency (BPS) and the Central Aceh Regency Government. The analysis was conducted using quantitative descriptive methods through the presentation of tables and graphs, accompanied by an examination of the GRDP–PAD relationship and indications of social change. The results show that the economic structure is dominated by the agriculture, forestry, and fisheries sectors, supported by trade, construction, and government services sectors, while service sectors such as accommodation, transportation, and financial services have experienced rapid growth following the XXI National Sports Week (PON XXI). GRDP and GRDP per capita have shown consistent increases; however, the PAD-to-GRDP ratio remains low, indicating that fiscal independence is not yet optimal. Economic development has implications for increased purchasing power, shifts in consumption patterns, livelihood diversification, and the emergence of a new middle class. These findings underscore the importance of downstreaming leading commodities, strengthening the regional tax base, and developing sustainable service sectors to promote fiscal independence and inclusive social development in Central Aceh. Keywords: Base Sectors; Central Aceh; Fiscal Independence; GRDP; Regional Original Revenue.